Enhancing the Interaction of Carbon Nanotubes by Metal–Organic Decomposition with Improved Mechanical Strength and Ultra-Broadband EMI Shielding Performance - Shi, Yu‑Ying; Liao, Si‑Yuan; Wang, Qiao‑Feng; Xu, Xin‑Yun; Wang, Xiao‑Yun; Gu, Xin‑Yin; Hu, You‑Gen; Zhu, Peng‑Li; Sun, Rong; Wan, Yan‑Jun (Nano-Micro Letters, 2024)
The remarkable properties of carbon nanotubes (CNTs) have led to promising applications in the field of electromagnetic interference (EMI) shielding. However, for macroscopic CNT assemblies, such as CNT film, achieving high electrical and mechanical properties remains challenging, which heavily depends on the tube–tube interactions of CNTs. Herein, we develop a novel strategy based on metal–organic decomposition (MOD) to fabricate a flexible silver–carbon nanotube (Ag–CNT) film. The Ag particles are introduced in situ into the CNT film through annealing of MOD, leading to enhanced tube–tube interactions. As a result, the electrical conductivity of Ag–CNT film is up to 6.82 × 105 S m−1, and the EMI shielding effectiveness of Ag–CNT film with a thickness of ~ 7.8 μm exceeds 66 dB in the ultra-broad frequency range (3–40 GHz). The tensile strength and Young’s modulus of Ag–CNT film increase from 30.09 ± 3.14 to 76.06 ± 6.20 MPa (~ 253%) and from 1.12 ± 0.33 to 8.90 ± 0.97 GPa (~ 795%), respectively. Moreover, the Ag–CNT film exhibits excellent near-field shielding performance, which can effectively block wireless transmission. This innovative approach provides an effective route to further apply macroscopic CNT assemblies to future portable and wearable electronic devices. Highlights: 1 A strategy based on metal-organic decomposition is proposed to enhance the tube-tube interactions of carbon nanotubes (CNTs). 2 The robust tube-tube interactions of CNTs enhance both EMI shielding performance and mechanical properties of CNT film. 3 This innovative approach provides an effective way to obtain high-performance CNT film.